Among Muslim Consumers in The World and Indonesia: Boycotting Israel-Affiliated Products’ Spirit - Marissa Grace Haque; Sulistyowati Sulistyowati; Meta Andriani; Edi Komara; Zulkifli Zulkifli (Return : Study of Management, Economic and Bussines, 2023)
It begins by exploring the historical and religious context of the boycott among the Muslim community, related to the situation in Medina and the impact of religious values on consumer behavior. This study discusses the reasons behind consumers' protests against foreign brands, emphasizing national identity, economic concerns, ethical factors, societal support, and perception factors that influence their behavior. Several characteristics of Muslim individuals, related to peer influence and group behavior, such as community and social ties, religious identity, influence of religious authority, solidarity with the global Muslim cause, sharing of information within the community, and a sense of responsibility. In addition, it explores the impact of religious motivation, intrinsic and extrinsic on consumer behavior, discusses the role of Islamic marketing and the use of symbols in influencing consumer behavior, emphasizes the global identity of the Ummah, and tailored marketing strategies. This methodology outlines the data collection and analysis process, highlighting the use of qualitative methods, to gain insight into consumer attitudes and motivations that drive boycotts across groups. Vosviewers is used for data analysis, to extract meaningful concepts and patterns from collected journals, identifying important themes and patterns. In conclusion, this research provides a comprehensive exploration of the motivations and dynamics of boycotts among Muslim consumers, highlighting the historical, religious, and socio-economic factors that influence consumer behavior and activism, a thorough investigation of the complex phenomenon of boycotts, insights into the dynamics of religion, culture, and social factors that shape consumer behavior.